Bone Marrow Erythropoiesis in the Anemia of Infection, Inflammation, and Malignancy - Zucker, Stanley (1974)
A major factor in the anemia of infection, inflammation, and malignancy is a relative failure of the bone marrow to increase erythropoiesis in response to a shortened red cell survival. The possible causes for this diminished marrow response are: (a) a reduced production of erythropoietin, or, (b) impaired bone marrow response to erythropoietin. In this report studies were performed on 6 normals, 13 patients with anemia from infection or inflammation, and 18 patients with anemia caused by advanced malignancy. Serum erythropoietin activity was measured using the posthypoxic, polycythemic mouse assay. Assessment of bone marrow response to erythropoietin was made by measuring (59)Fe-heme synthesis in bone marrow suspensions cultured for 3 days with and without the addition of erythropoietin. The results showed that marrow heme synthesis was increased in erythropoietin-treated cultures as compared with saline control cultures by 66±8% (mean ±SE) in normals, 101±10% in patients with infection or inflammation, and 31±5% in malignancy. Serum erythropoietin levels were consistently diminished relative to expected levels for the degree of anemia in the infection-inflammatory group, but not in malignancy. In these patients, plasma inhibitors to the biological activity of erythropoietin were not detected in vitro. These studies suggest that another factor to consider in the anemia of malignancy is a decreased bone marrow response to erythropoietin. In the anemia of infection-inflammation, marrow response to erythropoietin is normal, but serum levels of erythropoietin are decreased relative to the degree of anemia.